Trenggalek Durian Peel Ash a K2O Catalyst in Ultrasonic Biodiesel Production - Pitaloka, Dinda Ayu; Santoso, Aman; Hayuningtyas, Inggar Firdaus (Journal of The Indonesian Society of Integrated Chemistry, 2025)
Global population growth has driven increased demand for energy, particularly fossil fuels. A sustainable alternative to address this issue is the production of biodiesel from renewable sources, such as waste cooking oil. This study utilized a heterogeneous potassium oxide (K₂O) catalyst derived from local Trenggalek durian peel ash to enhance the efficiency of the transesterification reaction. The catalyst was synthesized via calcination at 400°C, 500°C, and 600°C for 5 hours. The transesterification reaction was carried out with a methanol-to-oil molar ratio of 12:1 and catalyst concentrations of 1%, 3%, and 5% (w/w) at 65°C. The optimum condition was achieved using durian peel ash catalyst calcined at 600°C at a concentration of 3% (w/w), yielding a biodiesel conversion of 96.24% via ultrasonic-assisted transesterification. The physicochemical characterization of the produced biodiesel showed results that met standard specifications, including analyses of yield, density, viscosity, refractive index, acid value, saponification value, and iodine value. Furthermore, FT-IR and GC-MS analyses were performed to confirm the functional groups and components of the biodiesel product, in accordance with the expected specifications.